Successful pathway for locally driven fuel cell electric vehicle adoption: Early evidence from South Korea - Hwang, Heeju; Lee, Youhyun; Seo, Inseok; Chung, Yanghon (International Journal of Hydrogen Energy, 2021)
South Korea is an outstanding pioneer of fuel cell electric vehicle (FCEV) technology, an industry that is fundamental to the hydrogen ecosystem. This study aims to explore possible pathways for the successful adoption of FCEV in the local region. By using the fuzzy-set quality comparative analysis (fs/QCA) method, we identify three auspicious pathways based on the 16 regional cases in Korea. We find that, first, a large number of hydrogen (H2) stations will lead to successful FCEV adoption (H2 STATION→FCEV). Second, the combination of high levels of greenhouse gases(GHGs) and the local government-driven future construction plans of H2 stations can also be a remarkable pathway (GHGs∗ PLAN→FCEV). Lastly, a combination of high levels of GHGs and subsidies can be another compelling pathway (GHGs∗ SUBSIDIES→FCEV). This study provides early evidence of FCEVs adoption and can be of use to latecomer countries to the hydrogen economy.
Keywords: Comparative analysis; Fs/QCA; Fuel cell electric vehicle; Greenhouses gas; Hydrogen economy; Local region; Pathway; South Korea; Vehicle technology; Fs/QCA; Fuel cell electric vehicle (FCEV); Hydrogen economy; Pathway